8(8-4x)-5=26+x

Simple and best practice solution for 8(8-4x)-5=26+x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8(8-4x)-5=26+x equation:


Simplifying
8(8 + -4x) + -5 = 26 + x
(8 * 8 + -4x * 8) + -5 = 26 + x
(64 + -32x) + -5 = 26 + x

Reorder the terms:
64 + -5 + -32x = 26 + x

Combine like terms: 64 + -5 = 59
59 + -32x = 26 + x

Solving
59 + -32x = 26 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
59 + -32x + -1x = 26 + x + -1x

Combine like terms: -32x + -1x = -33x
59 + -33x = 26 + x + -1x

Combine like terms: x + -1x = 0
59 + -33x = 26 + 0
59 + -33x = 26

Add '-59' to each side of the equation.
59 + -59 + -33x = 26 + -59

Combine like terms: 59 + -59 = 0
0 + -33x = 26 + -59
-33x = 26 + -59

Combine like terms: 26 + -59 = -33
-33x = -33

Divide each side by '-33'.
x = 1

Simplifying
x = 1

See similar equations:

| -5x^2-13x-6=0 | | 4f-9=15+8f | | m+22=15 | | (-3d^2-8+2d)+(4d-12+d^2)= | | m^2=90 | | 64x^2-16x=0 | | 5x^3+35x^2+5x+35=0 | | 38.8-9.7t=-67.9 | | 4b-5(7b+1)=-8b-28 | | 2a^2-9a+4=0 | | (u-8)(u+3)= | | 2(-1-9y)+4y=5 | | 18x^2-84x+98= | | 6(4x-7)=3(8x+8) | | 10n^2-4=506 | | 4+18r-2=9r+98-3r | | 159-4x=41x+14 | | 2x^3+5x^2-3x+5=0 | | 10-9x=23-16x | | x+(x-8)=60 | | 6y+4y=90 | | (8y-4y^2)+(3y-9y^2)= | | (0.5*x^2)-(1.5*x)=0.375 | | (0.5*x^2)-(1.5*x)-0.375=x | | q^2+2q=1 | | 2x^2-18x-8=0 | | 3x+30=10x-54 | | x^2-4.1x+2.2=0 | | (x^4)+(15x^2)-16=0 | | -7.5x=60.0 | | 3n-7=29 | | 0.7-10=0.5 |

Equations solver categories